2021
DOI: 10.3390/ani11113262
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of FSH Synthesis by Differentially Expressed miR-488 in Anterior Adenohypophyseal Cells

Abstract: Gonadotropin-releasing hormone (GnRH), which is synthesized and released by the hypothalamus, promotes the synthesis and secretion of follicle-stimulating hormone (FSH), thereby regulating the growth and reproduction of animals. GnRH analogues have been widely used in livestock production. MiRNAs, which are endogenous non-coding RNAs, have been found to play important roles in hormone regulation and other physiological processes in recent years. However, the roles of miRNAs in GnRH-mediated regulation of FSH s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Therefore, we attempted to administer low‐frequency GnRH intraperitoneally to rats similar to the cellular assay. Based on the changes in gonadotropins, we believe that our simulation was successful to a certain extent 26 …”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Therefore, we attempted to administer low‐frequency GnRH intraperitoneally to rats similar to the cellular assay. Based on the changes in gonadotropins, we believe that our simulation was successful to a certain extent 26 …”
Section: Discussionmentioning
confidence: 85%
“…The control group was injected with the same dose of saline. The specific preparation method of the GnRH injection solution was described in detail in our previous study 26 . Pituitaries were collected 10 min after the last injection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better explore the stimulatory effects of GnRH on pituitary and FSH, exogenous GnRH treatment of rats was attempted. In our previous study, it was also demonstrated that exogenous GnRH treatment increases gonadotropin secretion in rats [ 32 ]. In this study, we found that this stimulus, which promotes FSH secretion, did not affect the morphological structure of the adenohypophysis.…”
Section: Discussionmentioning
confidence: 99%
“…Adenohypophysis tissue and blood were collected 10 min after the second treatment for subsequent experiments. The specific protocol was described in detail in our previous research [ 32 , 50 ].…”
Section: Methodsmentioning
confidence: 99%